Exploring retro marketing with sport marketing professionals. Issue 3 (8th July 2019) - Scola, Zach; Gordon, Brian S.
Abstract : Purpose: The purpose of this paper is to expand our understanding of retro marketing in sport through the perspective of sport marketers. Design/methodology/approach: Fourteen sport marketers involved in their team's marketing and utilized retro participated in topical interviews. Interviews were transcribed and open coded to find themes around how retro marketing is utilized and why the marketers think it may be effective. Findings: This study discovered prominent themes explaining how retro marketing is implemented (changing marks and jerseys, celebrating anniversaries, milestones and past players and retro nights) and why it may be effective (nostalgia, retro design appeal and connection to the team's lived history). Originality/value: Despite the coverage of retro marketing in popular press, little is understood in the academic field. This current study should expand our understanding of retro marketing in sport and be effective in aiding future scholars who investigate retro marketing in sport.